No more machismo in Callyntra (Coleoptera: Tenebrionidae): Callyntra femina, a new species discovered based on female genitalia and genetic evidence - Zúñiga-Reinoso, Álvaro; Pinto, Pablo; Collado, Gonzalo A. (Zootaxa, 2018)
Callyntra is a genus of tenebrionid beetles endemic to the Southern Cone region of South America, with 23 species occurring in Chile and one shared with Argentina. The recent descriptions of new species were commonly based on the male genitalia structure, underestimating the utility of the female genitalia for this purpose. Analysis of the ovipositor structure of a series of females assigned to Callyntra carbonaria from the Bío-Bío and Araucanía in Southern Chile, have resulted in the discovery of a new species, Callyntra femina sp. nov., which was corroborated through molecular analysis using COI and 16S gene fragments. The phylogenetic analysis recovered C. femina as sister to a clade composed of C. rossi, C. carbonaria and C. riverai, being genetically more similar to C. rossi.